The Influence of Work Life Balance on Employee Performance at the Gowa Regency Education Office - Lily Mulfiani Syam; Sitti Nurbaya; Muhiddin Daweng (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine and analyze the influence of work life balance on employee performance at the Gowa Regency Education Office. The type of research used in this research is a quantitative approach. The population in this study were all employees of the Gowa Regency Education Office. The sample used in this research was 63 respondents taken using saturated sampling techniques. The data analysis technique used to test the hypothesis is simple linear regression analysis and t test (partial test) which is processed using statistical calculations through the Statistical for the Social Science (SPSS) application version 26. The results of this study show that Work Life Balance has a positive effect and significant impact on Employee Performance at the Gowa Regency Education Office as evidenced by the Work Life Balance (X) regression coefficient value of 0.789 and the calculated t value of 9.785 > t table 0.678 with a significant value of 0.000 < 0.05.